Analysis of learning needs of the Alternative Path of Puncak II community in Sukamakmur district, Bogor Regency. - Jaenal Mutakim (Direktorat Pendidikan Masyarakat dan Pendidikan Khusus, Direktorat Jenderal PAUD, Pendidikan Dasar, dan Pendidikan Menengah, 2019)
Abstrak: The key to successful of community empowerment is the implementation of education that is in accordance with the needs of the community. Learning needs of the community can be known by to use learning needs analysis. Information on adequate learning needs is needed to produce a strategy and ways to improve the quality of education, especially for people who cannot get educational opportunities on formal education.This study aims to find out the learning needs of the Alternative Path of Puncak II community in Sukamakmur District, Bogor Regency, West Java. The approach of this research is descriptive research using survey methods.The results showed the learning needs of the community were learning needs to foster motivation to work, learning needs to improve television, the need to learn the techniques of playing football, good moral learning needs, learning needs of Arabic, learning needs of agricultural science, the need to learn healthy dietary habits and nutritious, the need to learn good ways of speaking, learning needs to know how to become a good citizen, and the need to learn catering and workshop services.